Challenging Lower Extremity Open Wound Case: Limb-saving Reconstruction Technique in an Elderly Patient at Risk of Amputation - Ersin Yavuz; Berrak Karatan (Turkish Journal of Plastic Surgery)
Management of open wounds following lower extremity injuries remains a significant medical challenge. The presence of foreign materials, such as plates and screws, particularly after fractures, can lead to complications such as colonization and biofilm formation, resulting in recurrent wounds and impaired fracture healing. Various reconstructive techniques, ranging from simple to complex, are available for wound closure. However, distal lower extremity wounds pose unique challenges due to limited donor site availability and fewer reconstructive options. In cases of large defects or when exposed hardware cannot be removed, microsurgical-free tissue transfer is often preferred. However, factors such as advanced age, anesthesia-related risks, and comorbidities can reduce microsurgical success and complicate wound closure. We present a 90-year-old patient with an exposed medial and lateral plating site following a distal tibia and fibula fracture, along with active Kaposi’s sarcoma. Due to the patient’s advanced age, active Kaposi sarcoma and the high anesthesia risk of prolonged free flap surgery, a transtibial amputation was recommended by another center. Instead, we successfully managed the wound using a double local flap technique with appropriate postoperative care. This case highlights that, beyond microsurgical approaches, properly planned local flap techniques can serve as effective alternatives in selected patients. With careful surgical planning and appropriate wound management, complex lower extremity wounds in elderly patients can be successfully closed, preventing amputation and reducing morbidity and mortality. Our findings suggest that individualized treatment strategies provide limb salvage options in high-risk patients with wound healing challenges.